Prospective observational cohort study of symptom control prediction in paediatric asthma by using the Royal College of Physicians three questions. (December 2018) - Andrews, Glen; Lo, David; Richardson, Matthew; Wilson, Andrew; Gaillard, Erol
Abstract The Royal College of Physicians three questions (RCP3Q) is widely used for assessing asthma control within primary care in the UK, despite limited evidence in children. This study compared the RCP3Q as a tool for assessing asthma control in children (5–16 years) against the validated Asthma Control Test (ACT), Childhood Asthma Control Test (C-ACT), and Mini-Paediatric Quality of Life Questionnaire (MiniPAQLQ). We conducted a prospective observational cohort study involving children from eight primary care practices in Leicestershire. Children with doctor diagnosed asthma, or receiving regular asthma medication, were invited to participate. A total of 319 participants completed the MiniPAQLQ and the C-ACT/ACT questionnaires, before RCP3Q responses were collected as part of their routine asthma review conducted immediately afterwards. RCP3Q sensitivity for detecting uncontrolled asthma ranged from 43–60% and specificity from 80–82%. Using an RCP3Q score ≥2 to predict uncontrolled asthma and an RCP3Q score of zero to predict well-controlled asthma resulted in 10% of participants misclassified as uncontrolled and 8% as well-controlled, respectively. Using an RCP3Q threshold score of ≥1 resulted in 25% of participants being misclassified as uncontrolled. Our data suggests limited utility of the RCP3Q to assess asthma control in children. Alternative indicators of asthma control, such as the validated Asthma Control Test and the Children's Asthma Control Test should be considered instead. Childhood asthma: importance of validated control tests Validated asthma control tests should be used to assess children rather than the 'three questions' survey recently developed by the Royal College of Physicians. The UK-based organisation developed the RCP3Q as a practical, rapid way of assessing asthma control in primary care. However, the RCP3Q was never comprehensively trialed for use with children. Erol Gaillard and co-workers at the University of Leicester compared the RCP3Q with three validated tests and questionnaires to determine its efficacy in assessing patients aged 5 to 16. 319 child patients completed the validated tests and their RCP3Q responses were collected immediately afterwards on the same day. In comparison with validated tests, the RCP3Q varied in its accuracy depending on the threshold scores selected. A threshold score of 1 resulted in 25 per cent of participants being misclassified with uncontrolled asthma.